Electrodeposition and characterization of Zn–Sn alloy coatings from a deep eutectic solvent based on choline chloride for corrosion protection. (18th December 2014) - Fashu, S.; Gu, C. D.; Zhang, J. L.; Bai, W. Q.; Wang, X. L.; Tu, J. P.
<x xml:space="preserve">Abstract</x> With the aim of obtaining high corrosion resistant Zn–Sn alloy coatings from an ionic liquid, the effects of electrodeposition potential and electrolyte composition on the electrodeposition behavior, film composition, morphology and corrosion performance were investigated. Cyclic voltammograms indicate that Zn and Sn were co‐deposited at distinct reduction potentials as pure Zn and Sn elements. In addition, the phase composition analysis also showed that the obtained Zn–Sn alloy deposits (8 wt.%–45 wt.% Zn) consist of a two‐phase mechanical mixture of small aggregates of Zn and Sn metals. The Zn content of the alloy significantly increases as the electrodeposition potential and electrolyte Zn (II)/Sn (II) ratio increase. The corrosion performance study of the obtained Zn–Sn coatings showed that they have a passivation behavior and their corrosion resistance increases as the alloy‐Sn content increases. To improve their morphological properties, ethylene diamine tetraacetic acid additive was introduced into the electrolyte and greatly improved the morphology and corrosion resistance of the deposits. For the first time, it was shown that high corrosion resistance Zn–Sn coatings can be obtained from ionic liquids. Copyright © 2014 John Wiley & Sons, Ltd.